Genetic variability, correlation and path coefficient analysis in turmeric (Curcuma longa L.) - M Rajasekhar, V Sudhavani, R Rajyalakshmi, L N Naidu, (Journal of Spices and Aromatic Crops, 2013)
Eight turmeric genotypes were raised in a randomized block design to study the variability, heritability with genetic advance, correlation, direct and indirect effects of characters on rhizome yield for a period of four year. Variability accompanied by higher values for genetic coefficient of variation was recorded for rhizome yield. Heritability and genetic advance were high for rhizome yield and number of tillers per plant. In general, genotypic correlations were higher than phenotypic correlations for all the characters studied. Rhizome yield was positively and significantly correlated with plant height, number of tillers plant-1 and number of leaves plant-1. Number of tillers plant-1 followed by plant height exerted the highest positive direct effect on rhizome yield, which indicated that selection for these characters would directly improve the yield in turmeric.